ANALISIS KECEPATAN DAN GAYA HAMBAT MOBIL PADA TANJAKAN DENGAN SUDUT ELEVASI YANG BERBEDA - Lutfi Puspita Meliasari; Fatimah Putri Utami; Bayu Setiaji (Komunikasi Fisika Indonesia, 2023)
In this day and age almost everyone has private vehicles, especially cars. When driving using a car, you must always pay attention to the terrain traveled, such as uphill roads. When uphill, the car must resist obstacles, such as rolling inhibition force, incline drag force, and wind inhibition force. This study aims to determine the inhibitory force on the incline so that it must estimate the amount of gas speed of the car when passing the ramp, and can reduce the risk of accidents. In this study using quantitative methods with the help of tracker applications. This study resulted in an incline inhibition force when the car went uphill, namely in black cars of 2,112 N at a speed of 4,539 m/s, in black pick up cars of 1,350 N at a speed of 4,970 m/s, in white pick up cars of 1,166 N at a speed of 2,870 m/s, and on white cars of 1,840 N at a speed of 3,850 m/s.